ZNO nanostructured electrode fabrication for photovoltaic applications - Ramos, Carlos (2013)
Electrodes for Dye Sensitized Solar Cells (DSCs) were made using ZnO nanoparticles deposited over conductive substrates of SnO2:F (FTO). ZnO nanoparticles were obtained by the wet ball milling technique. Then these particles were used to make a viscous paste which was deposited over the substrate by the dr. lade method. After sintering, the electrodes were sensitized with organic and metalorganic dyes like D35 and N719 respectively during 14 hours. Liquid electrolytes with redox mediators like iodide/ triiodide redox cuple and cobalt complexes were used. Also platinum and polymer (PEDOT) covers were used like counterelectrodes. Sealed cells reported efficiencies values as high as 1.6% and values for incident photo conversion efficiency (IPCE) close to 60% at 500nm.